Analysing obsolescence, an elaborated model for residential buildings. Issue 3 (13th July 2015) - Thomsen, André; van der Flier, Kees; Nieboer, Nico
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – In previous research publications the authors combined the available knowledge about obsolescence in a conceptual model for further research on and appliance in the decision making about demolition. Since evidence-based theoretical research references on obsolescence are rare, the model inevitably had an explorative character. The purpose of this paper is to test and elaborate the model. Design/methodology/approach – A series of case studies were conducted in various residential building estates. In each estate the types of obsolescence (according to the model) and their interrelationships were identified. Findings – The model can usefully be applied; it enables the determination of types of obsolescence. The case studies also show that several types of obsolescence occur simultaneously, and that these types can be interrelated. This touches upon the complexity of cause-effect mechanisms as already mentioned in the introduction. One of the weaknesses is that information is sometimes available for only one point in time, and that the availability of information varies with the type of obsolescence. Research limitations/implications – The study is based on a limited selection of case studies. Further, the causal relationships between the types of obsolescence could not always be revealed. Practical implications – The current model does not distinguish between causes and effects. For further development of the model, cause-effect processes have to be further analysed. Social implications – Actual measurement of the extent of obsolescence per type is not part of this study, but has to be carried out before social implications can adequately be indicated. Originality/value – The paper presents a conceptual classification of obsolescence that turns out to be workable when tested in practice.